(untitled) (Mustansiria Dental Journal, 2018)
The aims of this in vitro study was to evaluate surface roughness (Ra) of four contemporary composite resin materials after applying home bleaching agent. Materials and Methods: Forty-eight composite specimens were made from four groups of different types composite resins (one-submicron hybrid, one microhybrid and two nanohybrid) of 12 specimens each: Group 1: Brilliant EverGlow, group 2: G-ænial from GC, group 3: Evetric and group 4: Ice, SDI. All the samples were polished with one step polishing system OptraPol. Each group was further subdivided into two subgroups (A&B) (n=6). Subgroups A were stored in distilled water as control, while subgroups B were bleached with 20% carbamide peroxide home bleaching agent for 14 day. Surface roughness analysis was then performed for all the samples using atomic force microscopy (AFM). Results were statistically analyzed using One-way ANOVA/LSD test analyzing the differences between the subgroups at p<0.05. Results: Surface roughness of all the groups increased after bleaching; however, LSD test showed significant differences that were only recorded between the subgroups of groups 3 & 4. Conclusion: 20% at-home bleaching treatment significantly affected surface roughness of both nanohybrid composite groups, while, it did not produce a significant surface changes for microhybrid and submicron composite resin.